Feasibility and Safety of Left Bundle Branch Pacing for Advance Aged Patients: A Multicenter Comparative Study - Ren, Zhongyuan; Cai, Binni; Wang, Songyun; Jia, Peng; Chen, Yang; Guo, Rong; Li, Hailing; Zhang, Jun; Xiong, Jing; Zhang, Jingying; Yang, Haotian; Li, Xiang; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Left bundle branch pacing (LBBP) has been shown to be a safe and effective means to achieve physiological pacing. However, elderly patients have increased risks from invasive procedures and the risk of LBBP in elderly patients is not known. We aimed to investigate the safety and efficacy of LBBP in elderly patients > 80 years of age. Methods: From December 2017 to June 2019, 346 consecutive patients with symptomatic bradycardia, 184 patients less than 80 years and 162 older than 80 years were included and underwent LBBP. The safety and prognosis of LBBP were comparatively evaluated by measured pacing parameters, periprocedural complications and follow-up clinical events. Results: Compared with the younger, the elderly group had worse baseline cardiac and renal function. LBBP was achieved successfully in both groups with comparable fluoroscopic time and paced QRS duration (110.0 [102.0, 118.0] ms for the young vs 110.0 [100.0, 120.0] ms for the elderly, P=0.874). Through a follow-up of 20.0±6.1 months, pacing parameters were stable while higher threshold and impedance were observed in the elderly group. In the evaluation of safety, overall procedure related complication rates were comparable (4.4% vs 3.8%, young vs elderly). For prognosis, similar major adverse cardiocerebrovascular events rate (7.1% vs 11.9%, young vs elderly) were observed. Conclusions: Compared to younger patients, LBBP could achieve physiological pacing in patients over 80 with comparable midterm safety and prognosis. While long-term safety and benefits of LBBP necessitate further evaluation.